Pengaruh Human Relation, Stres Kerja Dan Fasilitas Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Catatan Sipil Kota Tebing Tinggi - Safitri, Erika; Rusmewahni, Rusmewahni; Sinaga, Eka Mayastika (Management And Business Progress, 2024)
Human Resource Management is the science and art of managing the relationships and roles of the workforce so that they are effective and efficient in helping to realize the goals of the company, employees and society. The aim of this research is to determine the influence of human relations, work stress and work facilities on employee performance at the population and civil registration services of the city of Tebing Tinggi. The research method used is a quantitative research method. The sampling used in this research was the Non Probability Sampling method and the type of sampling used total sampling, the number of samples studied was 30 respondents. The analytisis tool used is multiple linear regression with the help of SPSS 25.00 Software. The results of this research show that human relations have a positive and significant effect on employee performance. Work stress has a positive and significant effect on employee performance. Work facilities have a positive and significant effect on employee performance. Human relations, work stress and work facilities simultaneously influence employee performance at the population and civil registration services of the city of Tebing Tinggi.